Avaliação do transporte transversal de sedimentos na praia estuarina de São Francisco – Ilha de Mosqueiro, Pará - NASCIMENTO, Carla Gabrielle Cardoso (2020)
Estuarine beaches are intermarine deposits of sand or gravel on the shores of estuaries. These deposits are mobilized by the action of river, tidal currents and local waves that originate erosion and sedimentary deposition zones. The São Francisco beach, located in Mosqueiro Island / PA, classified as an estuarine beach, where it has observed an erosive process arising from the action of the forcing mentioned. Given this, this study aimed to analyze the transverse sediment transport on this beach, in three sectors of it, in order to identify erosion, deposition or stability zones. Two field campaigns were carried out on 09/06/2019 (beginning of a lunar cycle) and 09/27/2019 (end of cycle), aiming to analyze the sedimentary balance (deposition and sediment removal) on the beach. Thus, results obtained for different oceanographic and meteorological conditions, since the study area is located in an estuarine sector of the coast of Pará, where the mentioned conditions control the oceanic action on the river. In the three studied sectors, sediments were collected from the transverse stream, using a trap in the sprawling zone, sometimes in the opposite direction to the river, sometimes in the opposite direction to the continent. Wave measurements were also made on the beach with ruler and filming. Then, analyzes were performed in the laboratory, with sieving techniques, aiming at the particle size separation of the sediments. The data obtained were later calculated to obtain the transverse sediment rate, the variations in the beach sedimentation during the flood and ebb tides and during the ebb and flow of waves in the three beach sectors. Analyzing the results, obtained with the sprawling trap, it was observed that during the flood tide of 06/09/2019, the volume of sediments carried transversely by waves and currents was higher analyzing a complete tide cycle, as well as the predominant grain size of this tide. The sector was coarse sand and medium sand, both during the wave flow and during the reflux of the waves. This scenario characterized a higher energy transverse transport during the flood tide of 09/06/2019. During this tidal phase there were higher wave heights. As the samples on 09/06/2019 occurred close to pre-sea, when the hydrodynamic conditions are higher at the site, intensifying the wave energy, greater sediment mobility was obtained than on 09/27/2019. The North sector showed a tendency towards imminent erosion, as it presented a sedimentary balance tending to equilibrium, due to the transverse sediment transport in the onshore direction being only slightly larger than the offshore direction.